2004
DOI: 10.1002/cncr.20109
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial meningeal hemangiopericytoma: The role of radiotherapy

Abstract: BACKGROUND The current retrospective study was undertaken to evaluate the treatment outcomes of patients with meningeal hemangiopericytoma (M‐HPC), to define the role of radiotherapy in the management of the disease, and to report on the patterns of failure. METHODS The medical records of 29 patients with nonmetastatic M‐HPC treated at The University of Texas M. D. Anderson Cancer Center (Houston, TX) between August 1979 and March 1999 were reviewed. Fifteen patients (52%) underwent macroscopic total resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
3
19

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(162 citation statements)
references
References 27 publications
(57 reference statements)
9
131
3
19
Order By: Relevance
“…Aggressive gross total resection (GTR) has been advocated by most as reports have found greater recurrence-free interval (RFI) and overall survival (OS) in patients [5,[17][18][19][20][21]. Schiariti et al [20] reported that patients with GTR had both longer mean OS (235 vs. 175 months, respectively; p = 0.47) and mean RFI (117 vs. 53 months, respectively; p = 0.0045).…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Aggressive gross total resection (GTR) has been advocated by most as reports have found greater recurrence-free interval (RFI) and overall survival (OS) in patients [5,[17][18][19][20][21]. Schiariti et al [20] reported that patients with GTR had both longer mean OS (235 vs. 175 months, respectively; p = 0.47) and mean RFI (117 vs. 53 months, respectively; p = 0.0045).…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…3,7,8,10,12,20) Total resection of HPC and adjuvant radiotherapy are effective. 8,20) Local control rates were 84% for total resections and 38% for partial resections (non-significant) 5 years after surgery, and no local recurrence was found after total resection and adjuvant radiotherapy, whereas local recurrence was found in 45% of patients without adjuvant radiotherapy after total resection (non-significant). 20) Preoperative radiotherapy caused tumor shrinking, resulting in less bleeding during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Intracranial HPCs represent less than 1% of all intracranial tumors and approximately 2%-4% of all meningeal tumors. 1,17,26,28,29 They almost always present as solitary, supratentorial (62%) dura-based lesions often arising from the falx, tentorium, dural sinuses, and skull base. Histopathologically, they are characterized by spindle cells with a rich vascular network, with large, dilated, "staghorn" vascular channels (Fig.…”
Section: Pathological Features and Presentationmentioning
confidence: 99%
“…Because of the high vascularity of the lesions, preoperative embolization can sometimes be advantageous. Soyuer et al 29 reported a superior 5-year local control rate in patients treated with GTR (84%) as compared with the rate in patients treated using subtotal resection (38%). Radiotherapy.…”
Section: Multimodal Managementmentioning
confidence: 99%
See 1 more Smart Citation